2004
DOI: 10.1111/j.1348-0421.2004.tb03620.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Probiotic Lactobacillus Strains on Jejunal and Cecal Microbiota of Broiler Chicken under Acute Heat Stress Condition as Revealed by Molecular Analysis of 16S rRNA Genes

Abstract: We examined the effects of probiotic Lactobacillus strains of Lactobacillus agilis JCM 1048 and Lactobacillus salivarius subsp. salicinius JCM 1230 on jejunal and cecal microbiota of broiler chicken under heat stress condition using terminal restriction fragment length polymorphism (T‐RFLP) analysis. The jejunal bacterial community was limited to a few bacterial groups, mostly Lactobacillus spp. A relatively abundant and higher prevalence of Lactobacillus spp. were observed in the jejunal and cecal microbiota … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
78
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 30 publications
0
78
1
1
Order By: Relevance
“…Previous study by Putsakum et al (2007) demonstrated no difference in the intestinal microbial populations between ACTH-treated and control birds, whereas in other studies environmental factors, such as stressful conditions influenced bacterial colonization of the gastrointestinal tract (Lan et al, 2004;Selig & Patterson, 2004;Gareau et al, 2007). As mentioned earlier, type and severity of stress and host intrinsic factors might explain the controversy among these reports.…”
Section: The South African Journal Of Animalcontrasting
confidence: 38%
See 1 more Smart Citation
“…Previous study by Putsakum et al (2007) demonstrated no difference in the intestinal microbial populations between ACTH-treated and control birds, whereas in other studies environmental factors, such as stressful conditions influenced bacterial colonization of the gastrointestinal tract (Lan et al, 2004;Selig & Patterson, 2004;Gareau et al, 2007). As mentioned earlier, type and severity of stress and host intrinsic factors might explain the controversy among these reports.…”
Section: The South African Journal Of Animalcontrasting
confidence: 38%
“…It has been reported that the GIT microflora cooperate in the development of the hypothalamus-pituitary-adrenal (HPA) axis (Sudo et al, 2004), which is necessary for the normal stress response. On the other hand, stressful experience can disturb the balance of the intestinal microbiota and lead to the excessive growth of pathogens while decreasing the proportion of beneficial bacteria such as lactobacilli and bifidobacteria (Fuller, 1999;Lan et al, 2004;Selig & Patterson, 2004;Lutgendorff et al, 2008). Thus, any changes in the GI tract microbiota due to stress may negatively influence HPA axis activities, for example, Gareau et al (2007) showed that maternal separation in mice increased blood corticosterone level as compared to the control.…”
Section: Introductionmentioning
confidence: 99%
“…Heat stress could induce the unfavourable changes in indigenous bacterial microbiota (Lin et al, 2006). The supplementation of probiotic Lactobacillus strains may aid in restoring the gut microbial balance of chicken having suffered heat stress (Lan et al, 2004).…”
Section: Mitigation Strategies To Ameliorate Heat Stress In Poultrymentioning
confidence: 99%
“…Pada penelitian terdahulu menunjukkan bahwa pemberian ekstrak etanol kulit batang jaloh dapat mengurangi stres dan memperbaiki performan ayam akibat cekaman panas (Sugito et al, 2007;dan Sugito, 2008). Adanya laporan hasil penelitian yang menyatakan bahwa pemberian probiotik (Lan et al, 2004, dan Ahmad, 2006 serta pemberian mineral kromium (Cr) juga dapat mengurangi dampak cekaman panas pada ayam broiler (Ahmad et al, 2004dan Toghyani et al, 2007, maka penggunaan ekstrak jaloh dikombinasikan pemberiannya dengan probiotik dan atau mineral kromium diharapkan dapat dioptimalkan efeknya dalam mengurangi gangguan fungsi tubuh akibat stres panas pada ayam. Tujuan dilaksanakannya penelitian ini adalah melihat pengaruh pemberian ekstrak jaloh bila pemberiannya dikombinasi dengan probiotik dan mineral kromium dalam air minumnya terhadap profil hematologi dan titer antibodi vaksin ND pada ayam yang mengalami cekaman.…”
unclassified